Colombia: A public-private partnership - Beintema, Nienke M.; Romano, Luis; Pardey, Philip G. (International Food Policy Research Institute, 2006)
Despite efforts in many Latin American countries to diminish the government role in the funding and performing of agricultural research and development (R&D), general government revenues are still the predominant source of support for agricultural research, as in many less-developed countries (Pardey and Beintema 2001). Colombia is an exception, evidenced by the presence of 12 nonprofit organizations, which together accounted for about a quarter of the country’s agricultural research investments in 2000. Many of these organizations are linked to producer organizations and are funded largely through export or production taxes or voluntary contributions.1 In addition, public agricultural research in Colombia underwent a major reform in 1993 with the creation of the Colombian Corporation for Agricultural Research (CORPOICA).2 The main objective of its creation was to give the agency more flexibility in its organization compared with its predecessor, the Colombian Agricultural Institute (ICA), in addition to stimulating privatesector involvement and investment. Nonetheless, CORPOICA remained heavily dependent on government contributions. In recent years, the agency’s funding situation has deteriorated, but this trend is common to all agricultural R&D agencies in Colombia as a consequence of the country’s ongoing economic and social crises.